PRECISION MEDICINE IN GERIATRIC CARE: HARNESSING THE POWER OF GENETIC PROﬁLING FOR PERSONALIZED THERAPIES IN OLDER ADULTS - Caiado, Fernanda Leal; Morii, Kelly Yumi; Alves, Maria Laura de Biasi; Destefani, Afrânio Côgo; Destefani, Vinícius Côgo (Revista Ibero-Americana de Humanidades, Ciências e Educação, 2024)
Precision medicine, an approach that tailors medical treatments to individual genetic proﬁles, holds immense potential for improving geriatric care. By leveraging pharmacogenomics and genetic proﬁling, personalized therapies can optimize treatment outcomes and minimize adverse effects in elderly patients. This narrative review explores the current state of personalized medicine in geriatrics, focusing on its applications in neurodegenerative diseases, psychiatric conditions, and other age-related disorders. We discuss the role of genetic markers in guiding treatment strategies, highlight the challenges and opportunities in implementing precision medicine in clinical practice, and provide future directions for research and translational efforts. As the ﬁeld continues to evolve, integrating genetic proﬁles into geriatric care offers a promising avenue for enhancing the efﬁcacy, safety, and quality of life for older adults.